Analisis Terhadap Putusan pengadilan Tata Usaha Negara yang terkait dengan Pembatalan Penerapan Pasal 87 ayat (4) UU ASN - Widyawati Boediningsih; Ingrid Angelina Lukiro Arif (Esensi Hukum, 2022)
This article or writing aims to analyze the process of resolving employment disputes with respect to civil servants based on applicable laws and regulations and the application of the provisions of article 87 paragraph (4) of Law number 5 of 2014 concerning State Civil Apparatus by state administrative officials. regarding the dishonorable discharge of civil servants in the perspective of the State Administrative Court. In analyzing, the juridical-normative legal research method is used. The data were collected through literature study. and analyzed qualitatively. This study concludes that the Civil Service Dispute Resolution Process with respect to the dismissal of civil servants is carried out by 2 (two) employment dispute resolution routes. In the PTUN Banda Aceh No. 9/G/2018/PTUN-BNA, dated 6 August 2018, the basis for dismissal for committing a criminal act of corruption which was sentenced to imprisonment based on the District Court Decision dated 23 February 2012 for 1 (one) year in prison. The substance of the application of the article in this decision applies Article 87 paragraph (4) letter b retroactively (retroactive principle). The reason for the cancellation is Article 28I paragraph (1) of the 1945 Constitution and is contrary to the principle of legal certainty.